ANALISIS KEBUTUHAN DAN KETERSEDIAAN AIR BERSIH DI WILAYAH KECAMATAN TIGO NAGARI KABUPATEN PASAMAN - Nofrizal, Nofrizal; Saputra, Robi Agung (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2021)
Clean water is one of the basic needs in supporting human life, as an area that is developing and experiencing regional expansion, Tigo Nagari District needs more and more water along with its development, especially clean water. With the increase in the infrastructure of Tigo Nagari District, it is certain that for the next few years, Tigo Nagari District will need even more clean water. In this study, an analysis of the need and availability of clean water was carried out in the Tigo Nagari District, Pasaman Regency. The analysis was carried out in the Tigo Nagari sub-district, which originates from the Batang Malandu river. In addition, this research will also evaluate the reservoir and distribution network in order to determine the current reservoir capacity and distribution network capability. Based on the results of the analysis, it was found that the total need for clean water in the Tigo Nagari District area in 2030 was 47.40 l / second, compared to the available discharge, the water source of the Batang Malandu river was still able to meet the needs of the population until 2030. evaluation results show that the reservoir capacity is still able to accommodate clean water needs.